William Randal Cremer (1828-1908): od syndykalizmu do pacyfizmu. Szkic biograficzny - Robak, Piotr (Acta Universitatis Lodziensis. Folia Historica, 2001)
The article presents the ideas and political activities of William Randal Cremer: an English worker and trade-unionist. The development of his political career was connected with the political struggle to democratize the British Constitution and to achieve peaceful state of international ralations in the second half of the 19th century. Cremer was one of the makers of the British trade-unionism in the 50’s of the century after the fall of the Chartist movement. He was in favour of solving the workers’ problems by means of trade-union’s peaceful mediation between the workers and their employers. In the 60’s Cremer and the British trade-unionism were engaged in the political action conducted by the Reform League (together with the radical wing of the Liberal Party) to introduce the next Reform Bill in the British Constitution and to create possibility for the British workers to sit in Parliament. At the same time Cremer participated in the formation and activity of the International Working Men’s Association but being a reformist he withdrew his support when the Association was taken over by revolutionary thinkers. Cremer didn’t also appreciate the political power of the working British mass risen in the 90’s: the new trade-unionism and the Independent Labour Party. For at reason when he had an occasion to sit in Parliament (thanks to the Reform Bill in 1885) as „Lib.-Lab.” he became a representative of radical liberals but not socialists. He was not involved in any of the British workers’ problems at the time. Cremer in Parliament and also in the various peace organisations (e.g. International Arbitration League), however, paid a lot of attention to advance his belief that peace was only acceptable state for manking and arbitration the method by which it could be achieved in international relations. As a result of his peaceful activities he became a laureate of the Peace Noble Prize in 1903. The idea of arbitration proved to be very important Cremer’s contribution to the world peace movement despite many tragic was experiences in the 20th century.